2020
DOI: 10.1073/pnas.1913433117
|View full text |Cite
|
Sign up to set email alerts
|

Splice variant of growth hormone-releasing hormone receptor drives esophageal squamous cell carcinoma conferring a therapeutic target

Abstract: The extrahypothalamic growth hormone-releasing hormone (GHRH) and its cognate receptors (GHRH-Rs) and splice variants are expressed in a variety of cancers. It has been shown that the pituitary type of GHRH-R (pGHRH-R) mediates the inhibition of tumor growth induced by GHRH-R antagonists. However, GHRH-R antagonists can also suppress some cancers that do not express pGHRH-R, yet the underlying mechanisms have not been determined. Here, using human esophageal squamous cell carcinoma (ESCC) as a model, we were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 50 publications
0
17
0
Order By: Relevance
“…GHRH also exerts direct extrapituitary activities 2 , 3 , such as cardioprotection 4 , 5 , regeneration of pancreatic islets 6 , wound healing 7 , as well as survival and antiapoptotic effects 8 , 9 . In addition, GHRH acts as an autocrine and/or paracrine growth factor in normal non-neoplastic cells and in cancers through the involvement of GHRH-R and its splice variant type 1 (SV1) 1 3 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…GHRH also exerts direct extrapituitary activities 2 , 3 , such as cardioprotection 4 , 5 , regeneration of pancreatic islets 6 , wound healing 7 , as well as survival and antiapoptotic effects 8 , 9 . In addition, GHRH acts as an autocrine and/or paracrine growth factor in normal non-neoplastic cells and in cancers through the involvement of GHRH-R and its splice variant type 1 (SV1) 1 3 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the asymptomatic feature of patients with early‐stage ESCC, most ESCC cases present in late stages [19, 20], with ∼48% of patients having stage III ESCC in our study. Thus, the potential impact of metformin in early developmental stages of ESCC ( i.e ., its influence on inhibiting the formation of tumor metastasis) remains to be determined.…”
Section: Figurementioning
confidence: 99%
“…For instance, the esophageal cancer promoting activities of the SV-1 splice variant of GHRHR, can potentially be blocked using the growth hormone-releasing hormone receptor antagonist MIA-602. 69 Additionally, all of the alternately spliced genes discussed in this review can be targeted using antisense oligonucleotide to silence those variants that promote cancer. At the same time studies have indicated that changes in alternate splicing associated with esophageal cancer, closely correlate with patient survival, suggesting the usefulness of alternate splicing profiles as prognostic biomarkers.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…The Splice variant 1 (SV1) is over-expressed in esophageal squamous cell carcinoma (Figure 3(II)). 69 Treatment of these cancers has been successful using GHRHR antagonists since certain forms of tumors have a high pGHRH-R content that reacts to antagonists of GHRH and GHRH-R. [70][71][72] It has been established that these antagonists act on the SV-1 splice variant to inhibit cancer growth and development. 69 The expression of this splice variant is also increased in response to hypoxia.…”
Section: Mage-a10mentioning
confidence: 99%